Isolation of actinomycetes from Sabah and the screening for inhibitor against Eukaryotic signal transdustion - Ho, Coy Choke; Lai, Ngit Shin (Universiti Malaysia Sabah, 2001)
Actinomycetes strains isolated from 504 soil samples collected from Sabah terrestrial ecosystem were studied and screened for novel bioactive compounds inhibitory against eukaryotic signal transduction. All the soil samples were collected under trees identified to species or genus level. Isolation of Streptomyces and non-Streptomyces actinomycetes on HV (humic acid + B-vitamins) medium yielded 569 strains. Morphology characterisation of the isolated actinomycetes was carried out including aerial mycelium, substrate colour, diffusible pigment and spore morphology- on oatmeal medium while chemotaxonomic identification based on Diaminopimelic Acid. All actinomycetes strains were grown under aerobic condition in liquid culture and extracted with acetone. In this research, yeast MAPK kinase and MAP kinase phosphatase are the molecular level targeted proteins. The screening system was developed for searching MAPK kinase and MAP kinase phosphatase inhibitors. MKKIP386 and MKKI P386-MSG5 mutant yeast were used to screen for inhibitors, as these yeast kinase and phosphatase have homologous proteins in the MAP kinase signal transduction pathway in human. Strain H7553 and H7597 showed potential MAPK kinase inhibitors. The in vivo RaslRaf interaction with the yeast two hybrid screening system was used to screen against RaslRaf protein interaction inhibitor. Strain H7520 showed potential inhibitor for yeast Type 1 protein serine/threonine phosphatase (GLC7) screening system. Extract H7944 showed inhibition effect in the ERK signal transduction (the chain-reaction of phosphorylation from MEK 112 to ERK 112) when inhibited phosphorylation of MEK to ERK. Thus, strain H7944 (MBA94-2) was able to prevent activation of MEK. Strain H7944 was a potential MEK 112 inhibitor since p-galactosidase assay confirmed that H7944 do not inhibited the Ras/Raf pathway.